Efisiensi Penggunaan Jumlah Bibit Terhadap Pertumbuhan dan Produksi Padi Sawah - Misran Misran (Jurnal Penelitian Pertanian Terapan, 2014)
The number of seedlings per hill of rice plants affects the level of productivity , the use of seeds per hill with the right amount of rice production. This research aims to determine the effect of the number of seeds/clump on the growth and production of rice. Research using randomized block design (RBD) consists of five treatments with four replications. The treatments tested were: A (1 seedling/hill), B (3 seedling/hill), C (5 seedling/hill), D (7 seedling/hill), and E (9 seedling/hill). The seeds used are Batang Piaman variety, 25x25 cm spacing. The experiment sites in lowland farmers Lubuk Minturun Sungai Lareh village, Koto Tangah district, Padang city, West Sumatra province on wed season 2009/2010. Fertilizer is given as 150 kg Urea, 100 kg SP36 and 75 kg KCl per hectare. Urea and KCl are given three times, with brocasting system at 7, 28, and 45 Days After Planting (DAP), while the SP36 is given at 7 DAP combined with Urea and KCl. The results showed the treatment number of seedlings provide significant effect (P<0.05) on the number of grains per panicle and grain yield. However, no significantly effect (P<0.05) on plant height, maximum number of tillers, number of productive tillers, panicle length, percentage of empty grains, and weight of 1000 grains. The use number of seedlings less than five seedling per hill produces the high number of seeds per panicle and grain yield per hectare. Based on these results it can be concluded that the number of seed on the rice crops are not more than five seedling per hill. Keywords: efficiency , number of seeds , production, lowland rice.